Identification of tumors with NRG1 rearrangement, including a novel putative pathogenic UNC5D‐NRG1 gene fusion in prostate cancer by data‐drilling a de‐identified tumor database. Issue 7 (24th February 2021) - Ptáková, Nikola; Martínek, Petr; Holubec, Luboš; Janovský, Václav; Vančurová, Jana; Grossmann, Petr; Navarro, Paloma Alcaraz; Rodriguez Moreno, Juan F.; Alaghehbandan, Reza; Hes, Ondřej; Májek, Ondřej; Pešek, Miloš; et al.
Abstract: The fusion genes containing neuregulin‐1 ( NRG1 ) are newly described potentially actionable oncogenic drivers. Initial clinical trials have shown a positive response to targeted treatment in some cases of NRG1 rearranged lung adenocarcinoma, cholangiocarcinoma, and pancreatic carcinoma. The cost‐effective large scale identification of NRG1 rearranged tumors is an open question. We have tested a data‐drilling approach by performing a retrospective assessment of a de‐identified molecular profiling database of 3263 tumors submitted for fusion testing. Gene fusion detection was performed by RNA‐based targeted next‐generation sequencing using the Archer Fusion Plex kits for Illumina (ArcherDX Inc., Boulder, CO). Novel fusion transcripts were confirmed by a custom‐designed RT‐PCR. Also, the aberrant expression of CK20 was studied immunohistochemically. The frequency of NRG1 rearranged tumors was 0.2% (7/3263). The most common histologic type was lung adenocarcinoma (n = 5). Also, renal carcinoma (n = 1) and prostatic adenocarcinoma (n = 1) were found. Identified fusion partners were of a wide range ( CD74, SDC4, TNC, VAMP2, UNC5D ), with CD74, SDC4 being found twice. The UNC5D is a novel fusion partner identified in prostate adenocarcinoma. There was no co‐occurrence with the other tested fusions nor KRAS, BRAF, and the other gene mutations specified in the applied gene panels. Immunohistochemically, the focal expression of CK20 was present in 2 lung adenocarcinomas. We believe it should be considered as an incidental finding. In conclusion, the overall frequency of tumors with NRG1 fusion was 0.2%. All tumors were carcinomas. We confirm (invasive mucinous) lung adenocarcinoma as being the most frequent tumor presenting NRG1 fusion. Herein novel putative pathogenic gene fusion UNC5D ‐ NRG1 is described. The potential role of immunohistochemistry in tumor identification should be further addressed.